Comparing Efficacies of Biopsy and Rapid Urease Testing for H. Pylori at a Single Institution - Kathleen Hill; Aiden V. Ohning; Jonathan P. Mallory; Stella Self; Christine M. G. Schammel; Jenny Meredith; John Reddic; Patrick Kent; Jenny B. Knight (Advanced Gut & Microbiome Research)
Helicobacter pylori (H. pylori) infects>50% of the world’s population, leading to gastric cancer if left untreated. An estimated 26,000 gastric cancer cases will occur in the US in 2023, with 40% of cases becoming the primary cause of death. Invasive and noninvasive techniques are used to diagnose H. pylori infection; however, controversy exists regarding the “gold standard” for diagnosis. We sought to evaluate the efficacy of H. pylori invasive detection methods: stained biopsy and rapid urease test (RUT) at a single institution. For the study, 200 patients (100 H. pylori + and 100 H. pylori -) from a single institution that underwent gastric biopsies were selected and retrospectively evaluated for H. pylori status. Demographics and clinicopathologic data were collected, including diagnostic tests performed, treatment, and outcomes. Histology and RUT were highly positively and negatively correlative; however, disparate results occurred in 7% of samples which was significant (p<0.001). Of those that were H. pylori positive, 60% had a posttreatment test completed. Gastric cancer developed in 3 patients (1.5%), all of whom were H. pylori positive. Histology and RUT testing yield similar results; therefore, there is no efficacious reason to run both tests on patients. Since histology has greater sensitivity (>95%) and the ability to identify other gastropathies, it should be considered the “gold standard,” for the identification of H. pylori.